Faktor-Faktor yang Mempengeruhi Tax Avoidance Pada Perusahaan Pertambangan Yang Terdaftar di BEI Tahun 2016-2018 - Husnia Najmah (Universitas Matana, 2020)
This study aims to examine and analyze the effect of profitability, leverage, company size, capital intensity, audit committee and sales growth on Tax Avoidance. The population in this study is mining companies on the Indonesia Stock Exchange (IDX) in 2016-2018. The sample was selected from the purposive sampling method and obtained a sample of 54 companies from several criteria. The data source is secondary data from the website (www.idx.co.id). This research uses multiple linear regression analysis with the help of SPSS version 20. The results of this research show that profitability, leverage, company size and sales growth do not have an influence on Tax Avoidance. While the capital intensity and audit committee have an influence on Tax Avoidance